FETO-MATERNAL OUTCOMES OF MATERNAL SEPSIS: A SNAPSHOT OF THE ILLNESS - Humaira Jadoon,; Iram Sarwar,; Fawad, Anisa; Salma Rehman,; Shehla Noor,; Maryam Bibi, (Journal of Ayub Medical College Abbottabad, 2023)
Abstract: Background: Maternal sepsis is a life-threatening condition with serious adverse feto-maternal outcomes. This descriptive cross-sectional study aimed to study the incidence of common feto-maternal outcomes of maternal sepsis in our hospital. Methods: Pregnant females with singleton pregnancy as per inclusion/exclusion criteria were enrolled in the study. A detailed medical history was taken and physical and obstetrical examination was done. They were investigated for the cause of their febrile illness and managed as per department protocols. Data was recorded in a pre-designed pro forma. Results: The most common cause of infection was UTI (32; 42.6%) followed by genital infections (20; 26.7%) and respiratory tract infections (15; 20%). In 8 (10.7%) patients, the cause couldn't be found. Only one patient developed sepsis and was admitted to the medical ICU. That pregnancy resulted in PROM and an infant with low birth weight was delivered. Both the mother and the child survived and were discharged from the hospital. There was no mortality in our study group. Conclusion: Though sepsis was associated with adverse feto-maternal outcomes in our study, the study design prevents us from drawing any conclusions from this study concerning maternal sepsis in our region. Further research is needed to determine the true magnitude of the problem.